Camrelizumab plus platinum-irinotecan followed by maintenance camrelizumab plus apatinib in untreated extensive-stage small-cell lung cancer: a nonrandomized clinical trial - Ni, Jun; Si, Xiaoyan; Wang, Hanping; Zhang, Xiaotong; Zhang, Li (Frontiers in Immunology, 2023)
Background: PD-L1 inhibitors plus chemotherapy have made substantial progress in extensive-stage disease small cell lung cancer (ED-SCLC), but the survival benefit is still limited. This study aimed to evaluate the preliminary efficacy and safety of camrelizumab plus platinum-irinotecan (IP/IC) followed by maintenance camrelizumab plus apatinib in untreated ED-SCLC. Methods: In this non-randomized clinical trial (NCT04453930), untreated ED-SCLC were enrolled and received 4-6 cycles of camrelizumab plus IP/IC, followed by maintenance camrelizumab plus apatinib until to disease progression or unmanageable toxicity. The primary endpoint was progression-free survival (PFS). Patients who received PD-L1 inhibitors (atezolizumab or durvalumab) plus platinum-etoposide (EP/EC) were selected as the historical control. Results: The baseline characteristics of the IP/IC plus camrelizumab group (N=19) and EP/EC plus PD-L1 inhibitor group (N=34) were balanced. The objective response rate (ORR) of IP/IC plus camrelizumab and EP/EC plus PD-L1 inhibitor was 89.6% and 82.4%, respectively. At a median follow-up time of 12.1 months, median PFS was 10.25 months (95% CI: 9.40-NA) in the IP/IC plus camrelizumab group and 7.10 months (95% CI 5.79-8.40) in the EP/EC plus PD-L1 inhibitor group, respectively (HR=0.58, 95% CI 0.42-0.81). The most common treatment-related adverse events (TRAE) in the IP/IC plus camrelizumab group was neutropenia, followed by reactive cutaneous capillary endothelial proliferation (RCEEP) and diarrhea. The occurrence of irAE was found to be associated with a prolonged PFS (HR=4.64, 95% CI: 1.92-11.18). Conclusions: IP/IC plus camrelizumab followed by maintenance camrelizumab plus apatinib showed preliminary efficacy and acceptable safety profile in untreated ED-SCLC.